Effects of row spacing on soil nitrogen availability, wheat morpho-physiological traits and radiation use efficiency - Zhang, Jie; Cao, Rui; Zhang, Zhiyong; Wang, Xiaochun; Ma, Xinming; Xiong, Shuping (Frontiers in Soil Science, 2022)
Optimizing row spacing is an important measure to exploit the full yield potential, achieve a continuous increase in wheat yield and green development without increasing input. The objective of this study was to compare the effects of wide–narrow row spacing pattern (12 cm-12 cm-12 cm-24 cm, R1) and conventional uniform row spacing mode (20 cm, CK; 12 cm. R2) on nitrogen (N) availability in soil, canopy structure, photosynthetic characteristics, radiation use efficiency (RUE) and yield. The results showed that R1 increased the relative abundance of ammonia-oxidizing bacteria and ammonia-oxidizing archaea in the rhizosphere compared to CK. Nitrate in soils treated R1 at post-anthesis and nitrogen use efficiency of the plant were 59.92% and 27.01% higher than those treated with CK, respectively. Above-ground growth of wheat showed that R1 increased leaf area index by 27.42%, specific leaf weight by 22.67% and leaf photosynthetic rate by 8.86%, respectively compared to CK. R2 had similar availability of N and plant growth as CK. Moreover, the ability of the plant to allocate more nitrogen to grains was enhanced at post-anthesis with R1 than it with CK and R2, which greatly improved the RUE by 10.13% and 2.27%. As the result, the yield for R1 increased by 27.54% and 21.46%, respectively, compared to CK and R2. Therefore, using wide–narrow row spacing pattern (R1) is a practically and environmentally feasible approach for wheat production without extra input in the straw-returning wheat-corn rotation system.